Nasal Discharge Eosinophils in Childhood Asthma Patients as a Predictive Factor for Persistent Asthma - Murayama, Norihide; Murayama, Kikuno (Mediators of Inflammation, 2018)
Objective. Eosinophilic inflammation is thought to play a role in childhood asthma. Thus, examination of nasal eosinophils, instead of sputum, may be useful for the diagnosis of not only eosinophil-positive rhinitis but also persistent asthma. Nasal eosinophil examination is a routine for the diagnosis of nasal eosinophil-positive rhinitis in patients with rhinorrhea symptoms. This retrospective study investigated whether testing for nasal discharge eosinophils is useful for diagnosing childhood allergic asthma and whether nasal discharge eosinophils are predictive of persistent asthma. Methods. Infants and young children (n=180) with at least 3 recurrent episodes of respiratory symptoms and bronchodilator inhalation improvements at intervals of ≥1 week were divided into the asthma group and the nonasthma group, and the presence or absence of nasal discharge eosinophils was examined by age. Correlations between nasal discharge eosinophils and other predictive factors for persistent asthma were also examined. Results. The evaluation of nasal discharge eosinophils in the asthma group showed a significantly higher positive rate in older age groups than in the 0–1-year-old age group (p<0.05–0.001). However, none of the asthma patient groups had any significant changes between the 0–1-year-old and older groups. This pattern was similar for other risk factors, showing correlations between nasal discharge eosinophils and other predictive factors. Conclusions. Testing for nasal discharge eosinophils with asthma symptoms increases with age. Nasal discharge eosinophils with asthma symptoms may be a predictive factor for persistent asthma. This trial is registered with UMIN Clinical Trials (registration number UMIN000030776).